E-Wallet Based Finplan Personal Design: Consumer Behavior Analysis - Faridah, Abdatul; farhan, ali; Kurniawan, Taufik (Universitas Islam Negeri Mataram, 2025)
This research aims to describe consumer behavior in planning finances through the use of e-wallets, which have been used since the COVID-19 pandemic and have become popular until now. The method used is a qualitative approach by collecting primary and secondary data through questionnaires and documents such as journals and books. Data analysis was carried out using a descriptive analysis method which aims to present the findings clearly and systematically. The results of this research show that consumer behavior in using e-wallets tends to be wasteful which is influenced by several factors such as impulsive shopping behavior, low income and lack of understanding of effective financial planning, all of which contribute to less than optimal financial management.